2003
DOI: 10.1007/978-3-540-39903-2_28
|View full text |Cite
|
Sign up to set email alerts
|

Hand-Held Steerable Needle Device

Abstract: Abstract. This paper presents a novel handheld device for steerable needle insertions for minimally invasive percutaneous procedures. Controlled lateral deflection of over 30mm during a 100mm axial insertion is demonstrated with a 20 gauge needle. A handheld, motorized device has been built to control the direction and rate of steering according to a two-axis miniature joystick input. To facilitate interventions with this steerable needle, two methods of locating the needle and its tip using ultrasound imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…Several flexible steerable needles have been developed in an effort to overcome the path planning limitations encountered with rigid straight needles (e.g., [2], [4][5][6][7][8][9]). Some of these newly developed needles rely on concentric axial insertion of multiple pre-bent needle parts, whereas others rely on reaction forces from the tissue to control the steering curvature (for reviews see [10,11]).…”
Section: Percutaneous Needles: a Brief State-of-the-artmentioning
confidence: 99%
“…Several flexible steerable needles have been developed in an effort to overcome the path planning limitations encountered with rigid straight needles (e.g., [2], [4][5][6][7][8][9]). Some of these newly developed needles rely on concentric axial insertion of multiple pre-bent needle parts, whereas others rely on reaction forces from the tissue to control the steering curvature (for reviews see [10,11]).…”
Section: Percutaneous Needles: a Brief State-of-the-artmentioning
confidence: 99%
“…In the future, the needle bending models will be validated in 3D using the ultrasound images exploiting the methods introduced in [13] .…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers have generated needle bending using different strategies such as incorporating a pre-bent stylet inside a straight canula [7], or a telescoping double canula where the internal canula is pre-bent [8]. Other researchers showed that needles with bevel tips bend more than symmetric-tip needles [9].…”
Section: Introductionmentioning
confidence: 99%